Optimization of process parameters for bioethanol production from oil palm frond juice by Saccharomyces cerevisiae using response surface methodology as a tool - Siti Hajar, Mat Zani; Faatihah, Mohamad Asri; Nina Suhaity, Azmi; Hafizuddin, Wan Yussof; Mior Ahmad Khushairi, Mohd Zahari (IOP Publishing, 2019)
The aim of this research was to investigate the effect of temperature, medium initial pH and rotation rate on the production of bioethanol from OPF juice without nutrient and nitrogen source supplementation using Saccharomyces cerevisiae Kyokai No. 7 (ATCC 26622). A five-level-three-factor central composite design (CCD) was employed in this study and the central point of each process variable was chosen based on the best condition obtained from the one-factor-at-time (OFAT) method. The parameters ranges were set as follows; medium initial pH (5-9), temperature (27.5-37.5°C) and rotation rate (80-120 rpm). Bioethanol and residual sugars concentration were determine using High Performance Liquid Chromatography (HPLC). The optimum conditions for bioethanol production from OPF juice were achieved at medium initial pH (6.62), rotation rate (96.51 rpm) and temperature (33.03°C). Based on the validation experiment, the optimum bioethanol yield was 0.50 ±0.02 g/g sugars and this value was in close agreement with the model prediction where the difference was only 4.17%. Under the optimal conditions, the bioethanol yield obtained was 47.06% higher compared with non-optimized condition. The promising yield obtained in this study suggests that OPF juice can be used as a renewable and complete fermentation feedstock for bioethanol production.